Investigation of the potential of Spleen Tyrosine Kinase (SYK) as a target for host-directed therapy during mycobacterial infection in macrophages - Mohapi, Sephekana Samuel (Department of Clinical Laboratory Sciences, 2022)
Tuberculosis (TB) is a communicable disease caused by a single infectious agent, Mycobacterium tuberculosis (Mtb). TB affects mostly the lungs and despite treatment being available, it still causes long term functional disability due to collateral tissue damage. The TBburden is exacerbated by the lengthy treatment period of 6-12 months which may result in issues of toxicity and poor adherence. Novel therapeutics are therefore urgently needed. Host directed therapies (HDT) are currently a promising way forward for limiting tissue pathology caused by Mtb. Spleen tyrosine kinase (SYK) plays an important role in innate immune signalling. It is expressed on innate immune cells such as macrophages. Macrophages play a critical role in thepathophysiology of TB. They are the first responders to Mtb infection and are phagocytic cells that engulf and destroy Mtb. They also produce inflammatory cytokines such as TNF and IL- 1β. Recent studies have suggested an involvement of SYK in the inflammatory signalling cascade linked to necrotic and caseous regions of granulomas of TB patients. However, it is unclear what role SYK plays in the pathophysiology of TB and whether its inhibition would result in resolution of excessive tissue damage in the lungs. Our study is based on an in vitro infection model of Thp-1 derived macrophages. We differentiated Thp-1 monocytes into macrophages and infected them with BCG or the pathogenic laboratory strain Mtb H37Rv. We then treated infected macrophages with SYK inhibitors; Fostamatinib and Piceatennol, collected supernatants and analyzed cytokine production using enzyme-linked immunosorbent assay (ELISA). Moreover, we also evaluatedwhether SYK inhibition with Fostamatinib or Piceatennol might affect the intracellular survival of Mtb in macrophages. We also attempted to confirm the reduced expression of SYK at geneand protein level after treating infected cells with Fostamatinib. Our data showed that Fostamatinib reduced the production of inflammatory cytokines IL-6, IL- 1β and TNF- in macrophages infected with BCG. Similarly, these findings were also observedin macrophages that were infected with Mtb H37Rv, with the exception of IL-1β that was unaltered in macrophages treated with Fostamatinib. Moreover, Fostamatinib reduced the production of anti-inflammatory cytokine IL-10 and the chemokine monocyte chemotactic protein-1 (MCP-1) in macrophages infected with Mtb H37Rv. We observed that Fostamatinibrescued macrophages from cell death induced by both BCG and Mtb H37Rv. Finally, we showed that treatment with Fostamatinib also reduced bacterial loads inside macrophages. In essence, our study showed that SYK inhibition attenuate Mtb induced inflammatory profile in macrophages and aids in macrophage anti-mycobacterial effects. Further, it suggests that SYK inhibition might be an attractive avenue to explore further as a potential host-directed therapy for TB.